2022
DOI: 10.3389/fimmu.2022.873382
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Ameliorates GMH-Induced Brain Injury by Regulating Microglia M1/M2 Polarization Via AdipoR1/APPL1/AMPK/PPARγ Signaling Pathway in Neonatal Rats

Abstract: Adiponectin (APN), a fat-derived plasma hormone, is a classic anti-inflammatory agent. Multiple studies have demonstrated the beneficial role of APN in acute brain injury, but the effect of APN in germinal matrix hemorrhage (GMH) is unclear, and the underlying molecular mechanisms remain largely undefined. In the current study, we used a GMH rat model with rh-APN treatment, and we observed that APN demonstrated a protective effect on neurological function and an inhibitory effect on neuroinflammation after GMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Furthermore, it has been frequently reported that adiponectin regulates macrophage polarization by acting on AMPK, NF-kB, and PPAR-γ signaling [ 20 , 34 , 35 , 36 , 37 , 38 ]. However, according to our results, it has no effect on cellular morphology and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been frequently reported that adiponectin regulates macrophage polarization by acting on AMPK, NF-kB, and PPAR-γ signaling [ 20 , 34 , 35 , 36 , 37 , 38 ]. However, according to our results, it has no effect on cellular morphology and migration.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, our study group analyzed the influence of adipokines, including leptin and adiponectin, on cementoblasts under compressive force stimulation, since adipose individuals showed worse outcome of orthodontic treatment [ 19 ]. In addition, adiponectin was reported to promote M2 polarization [ 20 ] and attenuate inflammation [ 21 ], and prevents tooth movement. Therefore, we assume it can intervene in the effects of compressive force on macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins were extracted from cells using the Keygen total protein extraction kit (Keygen, Biotech, Jiangsu, China) and then quantified by a bicinchoninic acid protein assay kit (Thermo Scientific, Waltham, MA, USA) as previously described [ 40 , 41 ]. The western blot experiments were performed according to standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term neurofunctional behavior was evaluated using righting reflex and negative geotaxis tests, which were conducted on days 1 to 3 post-GMH by independent researchers blinded to information on experimental groups, as previously described. 7,15 Water Maze Test…”
Section: Short-term Neurobehavioral Assessmentmentioning
confidence: 99%
“…As previously described, Morris water maze trials were conducted to assess memory and spatial learning on days 21 to 28 post-GMH. 7,17 Nissl Staining…”
Section: Short-term Neurobehavioral Assessmentmentioning
confidence: 99%